1977
DOI: 10.1056/nejm197709292971302
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Meningococcus Group A Capsular Polysaccharide Vaccine in Children Three Months to Five Years of Age

Abstract: We performed field trials in the course of an epidemic in Finland to learn whether Group A memingococcal capsular polysaccharide vaccine protects infants and young children from meningitis. The first trial involved 130,178 children between the ages of three months and five years; 49,295 children received the vaccine, 48,977 received a control Haemophilus influenzae Type b polysaccharide vaccine, and 31.906 remained unvaccinated. No cases of meningitis or sepsis caused by Group A meningococci were seen in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
120
1
8

Year Published

1979
1979
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(131 citation statements)
references
References 13 publications
2
120
1
8
Order By: Relevance
“…When volunteers were immunized with a group A polysaccharide vaccine so prepared, bactericidal antibody was produced. Although young children had a relatively poor antibody response, group A vaccine was shown to be successful in reducing the prevalence of MD in children as well as in adults (Peltola et al 1977). Group C polysaccharide vaccine has also been used successfully, for example in a controlled trial in service recruits in the United States (Artenstein et al 1970).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When volunteers were immunized with a group A polysaccharide vaccine so prepared, bactericidal antibody was produced. Although young children had a relatively poor antibody response, group A vaccine was shown to be successful in reducing the prevalence of MD in children as well as in adults (Peltola et al 1977). Group C polysaccharide vaccine has also been used successfully, for example in a controlled trial in service recruits in the United States (Artenstein et al 1970).…”
Section: Discussionmentioning
confidence: 99%
“…In South America an extensive outbreak was caused by group C, only recently recognized as capable of causing epidemic disease (de Morais et al 1974). During the past decade successful field trials have shown the efficacy of group A and C vaccine in preventing MD (Artenstein et al 1970;Peltola et al 1977). Because effective meningococcal vaccines are now avilable and because little is known of the prevalence of MD in Australia, we studied the prevalence of MD in South Australia and the serogroup distribution of isolates over a 10-year period.…”
Section: Introductionmentioning
confidence: 99%
“…Several kinds of vaccines against Neisseria meningitidis have been developed: polysaccharide (A, C, Y, W135) and conjugated (combining the capsular and non-capsular antigens). The effect of meningococcal vaccines is antigen-specific and age-dependent [18][19][20][21][22][23]. Meningococcal polysaccharide vaccines are not used in routine immunization programmes and their use depends on epidemiological indications [24,25]; most often, they are used for targeted vaccination of populations exposed during outbreaks, and in some countries for vaccination of military recruits [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Atualmente dispõe-se de vacinas polissacarídicas eficazes em conferir imunidade contra N. meningitidis A, C, Y e W135 17,21,29 . No entanto, crianças menores de 2 anos -a faixa etária de maior risco de aquisição da doença -desenvolvem baixos níveis de anticorpos bactericidas e conseqüentemente apresentam reduzidos níveis de proteção à doença 24,37,45 .…”
unclassified
“…Estudos realizados após a vacinação contra N. meningitidis A, em 1974 e 1975, na Finlândia, estimaram que concentrações de anticorpos contra o polissacáride A entre 1 e 2 ug/ ml, eram associadas com proteção à doença 37 . Segundo Kayhty e col. 28 , 1980, a duração da imunidade foi dependente da idade e do grau da resposta primária do indivíduo.…”
unclassified